2020
DOI: 10.7717/peerj.9656
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for stage and risk classification in head and neck squamous cell carcinoma (HNSCC)

Abstract: Machine learning techniques are increasingly used in the analysis of high throughput genome sequencing data to better understand the disease process and design of therapeutic modalities. In the current study, we have applied state of the art machine learning (ML) algorithms (Random Forest (RF), Support Vector Machine Radial Kernel (svmR), Adaptive Boost (AdaBoost), averaged Neural Network (avNNet), and Gradient Boosting Machine (GBM)) to stratify the HNSCC patients in early and late clinical stages (TNM) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Their dysfunction was closely related to many major diseases [ 12 ]. The forkhead box (FOX) family, composed of proteins that share related winged helix-turn-helix DNA binding motifs, belongs to the “winged helix” superfamily [ 13 ]. FOX genes are widely present in the evolution of vertebrates and invertebrates, involved in many molecular cascades and regulation of biological functions, such as embryonic development, cell cycle regulation, early morning metabolism control, and signal pathway transduction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their dysfunction was closely related to many major diseases [ 12 ]. The forkhead box (FOX) family, composed of proteins that share related winged helix-turn-helix DNA binding motifs, belongs to the “winged helix” superfamily [ 13 ]. FOX genes are widely present in the evolution of vertebrates and invertebrates, involved in many molecular cascades and regulation of biological functions, such as embryonic development, cell cycle regulation, early morning metabolism control, and signal pathway transduction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of high-throughput technologies such as gene chip and RNA sequencing, gene analysis has become a powerful tool for screening molecular biomarkers of tumour prognosis prediction ( 24 ). Recently, several studies demonstrated that the robustness of several biomarker combinations is better than the robustness of a single biomarker ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we extracted SNPs within 2 kb up-and down-stream regions of 8 differentially expressed autophagy-related genes using the Han Chinese in Beijing (CHB) data from the 1000 Genomes Project (March 2012) based on these selection conditions: (a) minor allele frequency (MAF) in population ≥ 0.05, (b) Hardy-Weinberg equilibrium (HWE) ≥ 0.05, (c) call rate > 95%. Secondly, SNPinfo Web Server (24), HaploReg (25), and RegulomeDB (26) were used to predict functional SNPs. SNPs were not included when the RegulomeDB score > 6.…”
Section: Clinical Assessment Of Crc Patientsmentioning
confidence: 99%
“…Statistical methods with univariate Cox regression analysis were utilized to assess associations between the clinical characteristics and OS of CRC patients (24). The results were corrected by the FDR, which was employed to mitigate against false-positive results.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation